2013
DOI: 10.1163/15685381-00002903
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and thermal regime effects on the specific dynamic action of Bothrops alternatus (Serpentes, Viperidae)

Abstract: bstract. Metabolic studies in ectothermic vertebrates are, almost always, conducted at a constant temperature, a valid and recommended procedure in most instances. However, for long term measurements, for example during snakes digestion, keeping experimental temperature constant subjects the animals to a condition potentially quite diverse from what animals may experience in nature. Thus, we investigated the influence of constant (20°C, 25°C, and 30°C) and fluctuating (circadian thermoperiod cycles of 20:30°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
(42 reference statements)
1
11
1
Order By: Relevance
“…In the present study, however, metabolic chambers were very small and movement of the lizards was limited. Some reptile species show a circadian rhythm in postprandial metabolic rate even in constant dark at a constant temperature in small metabolic chambers (Hare et al, 2006), whereas others do not (Gavira and Andrade, 2013). Still, the circadian rhythm observed in this study is stronger at the beginning of the trial when animals are digesting than later when the SDA response has (almost) ended.…”
Section: Circadian Rhythmcontrasting
confidence: 47%
See 2 more Smart Citations
“…In the present study, however, metabolic chambers were very small and movement of the lizards was limited. Some reptile species show a circadian rhythm in postprandial metabolic rate even in constant dark at a constant temperature in small metabolic chambers (Hare et al, 2006), whereas others do not (Gavira and Andrade, 2013). Still, the circadian rhythm observed in this study is stronger at the beginning of the trial when animals are digesting than later when the SDA response has (almost) ended.…”
Section: Circadian Rhythmcontrasting
confidence: 47%
“…Saito et al, 1975;Konturek et al, 2011;Dibner and Schibler, 2015). Postprandial pit vipers showed that snakes exposed to temperatures fluctuating between 30°C during photophase and 20°C during scotophase exhibited large changes in metabolic rates over several days of digestion (Gavira and Andrade, 2013), but we are not aware of any studies that have evaluated possible circadian rhythms in activity of digestive enzyme in reptiles. If the capacity of processing food is reduced at the end of the day, prey items captured early in the day may give the animals a greater profit (faster and better assimilation of the nutrients) than a prey captured in the afternoon.…”
Section: Circadian Rhythmmentioning
confidence: 90%
See 1 more Smart Citation
“…Physiological costs associated with the SDA response include both catabolic and anabolic processes (Andrade, Cruz‐Neto, Abe, Wang, & Starck, ; McCue, Guzman, & Passement, ; Secor, ), with protein synthesis identified as the most prominent contributor (Enok, Simonsen, & Wang, ; McCue, Bennett, & Hicks, ; Wang, Hung, & Randall, ). In ectothermic vertebrates, SDA is highly influenced by body temperature ( T b ), meal type, and meal size (Gavira & Andrade, ,b; Grayson et al, ; Powell, Mansfield‐Jones, & Gatten, ; Secor & Faulkner, ). The examination of the effects of these variables on the SDA response contributes to the understanding of the physiological and energetic implications associated with particular attributes of feeding biology.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, thermoregulation can be constrained by the availability of adequate thermal niches, and therefore most anurans routinely experience considerable variation in T b (Anderson, Bovo, & Andrade, ; Lillywhite, ; Noronha‐de‐Souza, Bovo, Gargaglioni, Andrade, & Bícego, ; Sievert, ). Variation in body temperature has an almost universal effect on the function of physiological systems (Bozinovic, Catalan, Estay, & Sabat, ; Bozinovic, Medina, Alruiz, Cavieres, & Sabat, ; Kern, Cramp, & Franklin, ; Niehaus, Angilletta, Sears, Franklin, & Wilson, ), including the metabolic rates while fasting and during meal digestion (Gavira & Andrade, ; Secor, ). In the latter case, an increase in T b is accompanied by higher postprandial metabolic rates and a shorter SDA duration (Powell et al, ; Secor, ; Secor & Faulkner, ; Secor, Wooten, & Cox, ).…”
Section: Introductionmentioning
confidence: 99%